Theory of Change Workbook: A Step-by-Step Process for Developing or St rengthening Theories of Change - Salib, Monalisa (USAID, 2022)
While over time theories of change have become synonymous with simple if/then statements, a strong theory of change should actually be a muc h more detailed, context-specific articulation of how we *theorize* ch ange will happen under a program.